A plasticidade do enredo do grêmio recreativo escola de samba Independentes de Boa Vista : como o desfile traduz o texto em imagem - Santos, Cristina Gonçalves dos (2019)
The present dissertation proposes to analyze the plasticity construction of the carnival parade of the Grêmio Recreativo de Escola de Samba Independentes de Boa Vista in the year 2018. The association, located in the municipality of Cariacica, participate